Ruta turística natural para la ciudad de Cariamanga, provincia de Loja - Rodríguez Flores, Ginger Paulina (2023)
The city of Cariamanga has a wide tourist potential with natural characteristics, it stands out for its great biodiversity, which is complemented by infrastructure, making these contribute to the progress of the city and promote respect for the conservation of biodiversity, and the redistribution of wealth by giving tourists the opportunity to be filled with unforgettable experiences by allowing them to participate in all activities, the same that must have adequate conditions for their enjoyment. The objective of this research was to design a natural tourist route for the city of Cariamanga, Loja Province. The first is to diagnose the situation of the natural tourist attractions in the city of Cariamanga, Loja Province, the second is to design a technical proposal to develop a natural tourist route for the city of Cariamanga, Loja Province, and finally, to elaborate tools for the promotion and dissemination of the natural tourist route for the city of Cariamanga, Loja Province. During the field research, the natural tourist attractions of the city of Cariamanga were identified, allowing to know the tourist activities that can be implemented in each tourist resource and generate a natural tourist route for the use and enjoyment of tourists, concluding that in the city of Cariamanga can develop various types of tourism such as sports and adventure tourism, ecotourism, gastronomic, etc., likewise, this tourist route was consolidated as a new tourism product, which provides tourist strengthening and hopes to increase the number of tourist visits which generates economic benefits for the locality.